Penguatan Ekosistem Pesisir: Monitoring dan Pembelajaran Pembangunan Alat Pemecah Ombak (APO) di Kota Semarang - Reny Yesiana; Itsna Yuni Hidayati; Gunawan Wicaksono (Jurnal Wilayah dan Lingkungan, 2016)
Climate change has been one of the major causes of environmental damage which needs to be anticipated early. In Indonesia, particularly in Semarang City, it has destroyed ponds and mangrove forests through erosion and sea level rise processes. The significant impact of climate change is exacerbated by the lack of public knowledge related to its threat, which in turn affects to the decrease in farmers’ income. This situation encouraged the Mercy Corps Indonesia in cooperation with the Government of Semarang Municipality and the Bintari Foundation to develop activities for strengthening the coastal area protection through the development of seawalls under the program named "Enhancing Coastal Community Resilience by Strengthening Mangrove Ecosystem Services and Developing Sustainable Livelihood in Semarang City". The construction of tires seawalls and Hybrid Engineering (HE) were completed in 2016. It had immediate impacts on the community in coastal areas. This article aims to review the monitoring of and the lesson learned from the seawalls construction for the communities in coastal areas, particularly in Genuk and Tugu Sub-districts. The methods used were mixed method research with a descriptive approach focusing on the analysis of measurable descriptive facts, which was supported by interviews for collecting tacit information in the community and reviews of archived reports on its development progress. The results showed that the seawalls development provides many positive effects for the community so that they are willing to maintain it for their own sake in the long term.